2021
DOI: 10.1111/jvim.16307
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal bacterial and fungal microbiota in normal horses and horses with nasopharyngeal cicatrix syndrome

Abstract: Background The nasopharyngeal bacterial and fungal microbiota of normal horses and those with nasopharyngeal cicatrix syndrome (NCS) are unknown. Hypotheses/Objectives To describe the microbiota from nasopharyngeal washes of healthy horses and of horses acutely affected with NCS. Animals Twenty‐six horses acutely affected with NCS horses and 14 unaffected horses. Methods Prospective, observational cohort study. Horses were recruited by investigators through personal communications in central Texas. Bacterial (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Limited information is available regarding the topography of the respiratory tract microbiota of horses 8,9,14,15 . A recent culture‐based study investigated the prevalence of fungi in respiratory samples of horses diagnosed with mild asthma and found that the presence of fungi in tracheal wash cytology doubled the likelihood of a horse having mild asthma 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited information is available regarding the topography of the respiratory tract microbiota of horses 8,9,14,15 . A recent culture‐based study investigated the prevalence of fungi in respiratory samples of horses diagnosed with mild asthma and found that the presence of fungi in tracheal wash cytology doubled the likelihood of a horse having mild asthma 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Limited information is available regarding the topography of the respiratory tract microbiota of horses. 8 , 9 , 14 , 15 A recent culture‐based study investigated the prevalence of fungi in respiratory samples of horses diagnosed with mild asthma and found that the presence of fungi in tracheal wash cytology doubled the likelihood of a horse having mild asthma. 16 Given that the overall bacterial composition of the respiratory tract contributes to various disease states, it is logical to question the role of the respiratory fungal microbiota in the healthy horse.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of sterile sampling method may be considered a limitation to this study. Pseudomonas was part of nasopharyngeal flora in 13 out of the 14 horses but was not included in the most prevalent genera found in the nasopharynx of healthy horses (Rodriguez et al, 2021). It is therefore possible that the Pseudomonas aeruginosa cultured from the fluid sample may have been a contaminant; however, the likelihood of this is considered low due to the pure growth rather than a mixed growth including other, more prevalent, microflora genera in the nasopharynx.…”
Section: Discussionmentioning
confidence: 99%